2021
DOI: 10.3892/ijo.2021.5227
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑153‑3p suppresses retinoblastoma cell growth and invasion via targeting the IGF1R/Raf/MEK and IGF1R/PI3K/AKT signaling pathways

Abstract: Mounting evidence has demonstrated that microRNAs (miRNAs or miRs) play significant roles in various types of human tumors, including retinoblastoma (RB). However, the biological role and regulatory mechanisms of miRNAs in RB remain to be fully elucidated. The present study was designed to identify the regulatory effects of miRNAs in RB and the underlying mechanisms. Differentially expressed miRNAs in RB tissue were screened out based on the Gene Expression Omnibus (GEO) dataset, GSE7072, which revealed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Currently, some studies have reported that the PI3K/Akt pathway plays an important role in RB [ 21 23 ]; however, the anticancer effect of eriodictyol on RB has not been reported. The purpose of this study was to investigate the antitumor effect of eriodictyol on the retinoblastoma Y79 cell line and its potential mechanism of action and to provide a new basis for tumor therapy with the PI3K-Akt signaling pathway as a key molecular target.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some studies have reported that the PI3K/Akt pathway plays an important role in RB [ 21 23 ]; however, the anticancer effect of eriodictyol on RB has not been reported. The purpose of this study was to investigate the antitumor effect of eriodictyol on the retinoblastoma Y79 cell line and its potential mechanism of action and to provide a new basis for tumor therapy with the PI3K-Akt signaling pathway as a key molecular target.…”
Section: Introductionmentioning
confidence: 99%
“…IGF1R is a trans -membrane tyrosine kinase receptor and frequently up-regulated in breast cancer [ 27 ]. The interaction between the molecules IGF-I and IGF-II, along with the receptor IGF1R, triggers powerful signals that promote cell growth and prevent cell death via the pathways PI3K/AKT and RAS/MAPK [ 28 ]. It suggests that in luminal breast cancer with a PIK3CA mutation, MAPK1/3 phosphorylation may play a critical role as a downstream effector worth targeting [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research into novel biomarkers is an effective way to improve the probability of satisfactory outcomes, including the prognosis and quality of life in patients with retinoblastoma. Although new molecular biomarkers for retinoblastoma have been revealed in recent years [7][8][9][10][11], they are still in the experimental stage and have not been approved for clinical use [12]. Currently, there is no gold standard biomarker for the diagnosis and treatment of retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%